Academic Publishing in Nepal - Ravi Shankar, Pathiyil; KC, Bhuvan; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2022)
Globally academic publishing is a high-profit industry. Most of the work associated with manuscripts is carried out byacademics for free. The article examines the academic publishing industry in Nepal. Most journals in Nepal are publishedby institutions or societies. Most do not have article processing charges. The issue of Nepalese authors having to pay forpublishing in international journals as Nepal is upgraded to a lower-middle-income country is also mentioned.